Effect of biomass power plant ash on fresh properties of cemented coal gangue backfill. (18th July 2022) - Qi, Tingye; Gao, Xinyu; Feng, Guorui; Bai, Jinwen; Wang, Zehua; Chen, Qiusong; Wang, Haochen; Du, Xianjie
Graphical abstract: Highlights: The introduction of biomass power plant ash (BPPA) could improve the fresh properties. The influence mechanism of BPPA on the fresh properties was obtained. The appropriate replacement rates of BPPA for cement and fly ash were obtained. Abstract: To improve the performance of coal mine cemented backfill materials and reduce the cost, biomass power plant ash (BPPA) is introduced to the preparation of coal gangue backfill materials, and the influence of BPPA on the fresh properties of cement coal gangue backfill (CCGB) is studied by using BPPA partially replaced cement and fly ash in the raw material. Slump and spread test, bleeding rate test, and setting time test were taken to evaluate fluidity, water retentivity, and setting time of CCGB at different substitution amounts (0, 10, 20, 30, and 40 wt%). At the same time, the Zeta potential tests, hydration heat tests, and water film thickness (WFT) theory is used to explain the results of the fresh properties tests. The replacement of cement and fly ash by BPPA improved fluidity and water retentivity of fresh CCGB while meeting the requirement of setting time; To ensure that CCGB has good fluidity and uniformity, it is recommended that the replacement rate should be greater than 10% when BPPA replaces cement, the replacement rate should not exceed 20% when BPPA replaces fly ash. The results show that BPPA can significantly improve the fresh properties of CCGB, which can be used for the preparation of cemented coal gangue backfill material. Meanwhile, the influence mechanism is explained, which has guiding significance for the application of BPPA cemented backfill material in engineering practice.